Pengaruh Keamanan,Kesehatan Kerja Terhadap Kinerja Karyawan di PT. Raihan Cipta Abadi - Hermin Andi Magga (STIM-LPI Makassar, 2023)
This study aims to determine the effect of safety, occupational health on employee performance at PT.Raihan Cipta Abadi. The research method used in this study is a quantitative approach. The population in this study were all employees of PT.Raihan Cipta Abadi. The sampling technique used is saturated sampling where the entire population is a sample of 57 people. Data collection techniques using a questionnaire. The collected data is processed using SPSS. Based on the results of the study it was concluded that the security variable (X1) has a significant effect on employee performance (Y) partially as evidenced by a sig value of 0.026 <0.05. And the variable health (X2) is the variable that has the most significant effect on employee performance (Y) partially as evidenced by a significance value of 0.030 <0.05. Therefore, in this study hypotheses 1, 2 and 3 are accepted. It is recommended that companies provide encouragement to employees and pay attention to the safety and health of their employees.